2021
DOI: 10.1177/11206721211012862
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate intake and risk of glaucoma in the sun cohort

Abstract: Purpose: To assess the association between carbohydrates (CH) intake and glaucoma incidence. Methods: 18,247 volunteer participants (183,067 person-years at risk) with 10-year of median follow-up were included in this prospective dynamic cohort. Baseline total CH intake (g/d) was categorised in quartiles and classified in nine different CH food sources. Self-reported diagnosis of glaucoma was collected at baseline and on biennial follow-up questionnaires. CH intake and glaucoma diagnosis were validated in a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Alcohol use has not been associated with visual field defect deterioration in known glaucoma patients, 89 progression from POAG suspect to definite POAG, 90 or progression to blindness in high-tension POAG. 91 Alcohol consumption was also not found to be associated with incident self-reported glaucoma in the SUN cohort 92 or with prevalent glaucoma in a German case-control study. 93 …”
Section: Discussionmentioning
confidence: 93%
“…Alcohol use has not been associated with visual field defect deterioration in known glaucoma patients, 89 progression from POAG suspect to definite POAG, 90 or progression to blindness in high-tension POAG. 91 Alcohol consumption was also not found to be associated with incident self-reported glaucoma in the SUN cohort 92 or with prevalent glaucoma in a German case-control study. 93 …”
Section: Discussionmentioning
confidence: 93%
“…Glaucoma was defined, following the European Glaucoma Society recommendations, as a visual field defect with damage to the optic nerve rim and loss of retinal nerve fibers. A correct glaucoma diagnosis was found in the validation study performed, with a Kappa value of 0.85 (95% coefficient interval (CI), 0.83-0.87) and good sensitivity (0.83) and specificity (0.99) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The validation results showed high agreement between self-reported and clinical diagnoses (kappa (κ) = 0.85; 95% CI 0.83 to 0.87) and high specificity (0.99) and sensitivity (0.83). All validated diagnoses were open-angle glaucoma [17].…”
Section: Glaucoma Incidence (Dependent Variable)mentioning
confidence: 99%
“…Although there is limited evidence linking diet to glaucoma, previous research has suggested connections between nutrition and glaucoma risk [17][18][19][20]. For example, a greater consumption of carbohydrates has been related to an increased risk of developing glaucoma [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation